Advances in physical ergonomics and safety - Ahram, Tareq Z.; Karwowski, Waldemar, 1953- (Boca Raton : CRC Press, 2013)
"Preface The discipline of human factors and ergonomics (HF/E) is concerned with the design of products, process, services, and work systems to assure their productive, safe and satisfying use by people. Physical ergonomics involves the design of working environments to fit human physical abilities. By understanding the constraints and capabilities of the human body and mind, we can design products, services and environments that are effective, reliable, safe and comfortable for everyday use. A thorough understanding of the physical characteristics of a wide range of people is essential in the development of consumer products and systems. Human performance data serve as valuable information to designers and help ensure that the final products will fit the targeted population of end users. Mastering physical ergonomics and safety engineering concepts is fundamental to the creation of products and systems that people are able to use, avoidance of stresses, and minimization of the risk for accidents. This book focuses on the advances in the physical HF/E and safety, which are a critical aspect in the design of any human-centered technological system. The ideas and practical solutions described in the book are the outcome of dedicated research by academics and practitioners aiming to advance theory and practice in this dynamic and all-encompassing discipline. "--
section 1. Safety and health -- section 2. Work related musculoskeletal disorders -- section 3. Ergonomics and system design -- section 4. Ergonomic methods and task analysis.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Human engineering; Design -- Human factors; Manufacturing processes -- Human factors; Industrial safety; Electronic books